(untitled) - Montgomery, Douglas C. (Hoboken, NJ, 2005)
Douglas Montgomery arms readers with the most effective approach for learning how to design, conduct, and analyze experiments that optimize performance in products and processes. He shows how to use statistically designed experiments to obtain information for characterization and optimization of systems, improve manufacturing processes, and design and develop new processes and products. You will also learn how to evaluate material alternatives in product design, improve the field performance, reliability, and manufacturing aspects of products, and conduct experiments effectively and efficiently.
Thiết kế và phân tích thí nghiệm,Thiết kế thí nghiệm và xử lý số liệu,Thiết kế thực nghiệm và tối ưu hóa,Thống kê phép thí nghiệm ứng dụng trong DT&CGCT
Keywords: Experimental design,Thiết kế thí nghiệm